Kamishoyosan and Shakuyakukanzoto promote recovery from paclitaxel-induced neurite retraction in PC12 cells - Konaka, Ken (J Pharm Health Care Sci, 2017)
BACKGROUND: In chemotherapy, the full round of treatment must be completed as scheduled to achieve the strongest therapeutic effect. However, peripheral neuropathy, a severe side effect of the chemotherapeutic agent paclitaxel, can force the premature discontinuation of treatment. As some kampo practitioners have suggested that it may be possible to counteract such side effects, we analyzed the effects of Kamishoyosan, Shakuyakukanzoto, and Goshajinkigan in an in vitro model of paclitaxel-induced peripheral neuropathy. METHODS: Paclitaxel-treated PC12 cells were assessed for neurite length and performed Western blot analysis for growth-associated protein-43 (GAP-43) and light neurofilament protein (NF-L) levels in the presence of nerve growth factor (NGF); they were re-assessed, with additional testing for acetylcholinesterase levels, after application of one of the kampo. We also compared phosphorylation of extracellular signal-regulated kinase (Erk)1/2 and Akt via Western blot analysis. About effect of kampo to anticancer efficacy, we confirmed cell cytotoxicity in A549 cells using MTT assay. RESULTS: Addition of Kamishoyosan or Shakuyakukanzoto, but not Goshajinkigan, significantly improved neurite length and GAP-43 and NF-L levels from paclitaxel-treated PC12 cells, relative to those of only NGF-treated PC12 cells. The promoting effect of Kamishoyosan and Shakuyakukanzoto in neurite outgrowth is confirmed when NGF promoted neurite outgrowth, and it was inhibited partially when Erk1/2 and Akt were blocked by Erk1/2 inhibitor or Akt inhibitor alone. Furthermore, neurite outgrowth induced by TJ24 and TJ68 was inhibited more strongly when Erk1/2 inhibitor and Akt inhibitor were treated at the same time. NGF with Kamishoyosan or Shakuyakukanzoto promoted the proportion of phosphorylated Erk1/2 and phosphorylated Akt compare with NGF only. On the other hand, Kamishoyosan or Shakuyakukanzoto didn’t influence cytotoxicity of paclitaxel in A549 cells. CONCLUSIONS: Kamishoyosan or Shakuyakukanzoto promotes neurite outgrowth with NGF via increasing the proportion of phosphorylated Erk1/2 and phosphorylated Akt in PC12 cells. The effect applies to recovery from paclitaxel-induced axonal involvement and might promote recovery from paclitaxel-induced neuropathy without influence of anticancer effect of paclitaxel.